Membrane Localization of Piezo1 in the Context of Its Role in the Regulation of Red Blood Cell Volume - Božič, Bojan; Svetina, Saša (Frontiers in Physiology, 2022)
Piezo1 is a membrane nonspecific cation channel involved in red blood cells (RBCs) in the regulation of their volume. Recently, it was shown that it is distributed on the RBC membrane in a nonuniform manner. Here it is shown that it is possible to interpret the lateral distribution of Piezo1 molecules on RBC membrane by the curvature dependent Piezo1 – bilayer interaction which is the consequence of the mismatch between the intrinsic principal curvatures of the Piezo1 trimer and the principal curvatures of the membrane at Piezo1´s location but without its presence. This result supports the previously proposed model for the role of Piezo1 in the regulation of RBC volume.